Number size distribution of atmospheric particles in a suburban Beijing in the summer and winter of 2015. (August 2018) - Du, Peng; Gui, Huaqiao; Zhang, Jiaoshi; Liu, Jianguo; Yu, Tongzhu; Wang, Jie; Cheng, Yin; Shi, Zongbo
Abstract: Particle number size distribution in a suburban Beijing was measured during the HOPE-J3A (Haze Observation Project Especially for Jing–Jin–Ji Area) field campaigns in 2015 from 18 June to 23 July (summer) and 2 to 25 December (winter). Average particle concentrations during the summer and winter campaigns were 9.6 ± 4.8 × 10 3 cm −3 and 13.9 ± 8.3 × 10 3 cm −3, respectively. Particle numbers were dominated by Aitken mode particles in both seasons. During the winter campaign, pollution events occurred every four to five days, each lasting for two to three days. In contrast, pollution events lasted for one to two days every six to seven days during the summer campaign. Aitken mode particles were 50% higher in the winter but new particle formation (NPF) events occurred more frequently in the summer. NPF events usually starts at around 10:00 LT (local time) in the summer but 12:00 LT in the winter. Aitken and accumulation mode particles accounted for 43.5% and 38.2% of all particles. The proportion of Aitken mode to total particles remained almost the same during summer, while it increased as haze intensified in winter. Particle number concentration was closely correlated with traffic and residents living activities and wind speed, with higher concentrations during rush hours, heating period and in the southerly wind. These results, when combined with trajectory cluster analysis, suggest that Aitken and accumulation mode particles were mainly from regional transport during the summer campaign, but from vehicle and coal-combustion emissions during the winter campaign. Graphical abstract: Image 1 Highlights: Particle numbers were dominated by Aitken mode particles in summer and winter. Concentrations of each mode particles in winter were higher than those in summer. Total particle number concentration was higher in the southern wind. Potential sources of each mode particles in winter and summer were studied.